PERANCANGAN APLIKASI LAPORAN KEUANGAN PADA UD. PUTRA KEMBAR - Putri; Marlina; Selao, Ahmad; Masnur (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
SMEs often face challenges in efficient financial management, particularly in transaction recording and the preparation of accurate financial reports. This study aims to design a financial report application that can improve the efficiency and accuracy of financial management at UD. Putra Kembar, a building materials trading business. The designed application features tools to record daily transactions and generate automated income statements, balance sheets, and cash flow reports. This research employs a quantitative approach with a descriptive and experimental design. The sample consists of 30 respondents directly involved in financial management at UD. Putra Kembar. Data were collected through a questionnaire measuring the benefits of the application, ease of use, and system quality. The results indicate that the financial report application accelerates transaction recording, reduces recording errors, and generates more accurate reports. The majority of respondents found the application easy to use, even without technical backgrounds. Overall, this study contributes significantly to the application of technology in SME financial management, particularly in terms of efficiency, accuracy, and ease of use. This application is expected to provide an effective solution for other SMEs to improve their financial management.